Digital Musical Instruments, Accessibility, and Facilitated Performance - Dickens, Amy (2023)
A range of bespoke devices, ADMIs, and commercially available DMIs are used in inclusive music settings when creating, practising, and performing music. However, the shared knowledge about what makes an existing DMI accessible is limited. This thesis investigates the accessibility of existing DMIs using participatory action research methods to establish more standardised methods for evaluating accessibility. Additionally, this research explores how DMIs are used in inclusive music settings to provide access to music-making activities using the theoretical framework of activity theory.